2014
DOI: 10.1097/brs.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Increased Surgical Drain Output After Anterior Cervical Discectomy and Fusion

Abstract: Study Design Retrospective cohort study. Objective To identify factors that are independently associated with increased surgical drain output in patients who have undergone ACDF. Summary of Background Data Surgical drains are typically placed following ACDF to reduce the risk of complications associated with neck hematoma. The orthopaedic literature has repeatedly challenged the use of surgical drains following many procedures, and there are currently no guidelines for determining which patients are most l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…[ 9 ] The primary outcome measure was increased drainage, and we defined this binary variable as positive when the drainage was greater than or equal to the 50th percentile of drainage for this cohort. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 ] The primary outcome measure was increased drainage, and we defined this binary variable as positive when the drainage was greater than or equal to the 50th percentile of drainage for this cohort. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“… 31 Along with that anemia was associated with an increased length of hospital stay, an important marker of hospital costs and predictor of adverse outcomes in high-risk spinal surgery. 32 , 33 Given that in most cases minimal blood loss and transfusions are required for ACDF surgery, 34 , 35 the association between anemia with complications in this study suggests that anemia may be a proxy variable that indicates patients’ general poor health, rather than having a direct bearing on surgery itself. Anemia is multifactorial and more so related to patient comorbidities, which include some confounders that could not be accounted for in the present multivariable analysis.…”
Section: Discussionmentioning
confidence: 85%
“…A thorough understanding of the development of increased surgical drain output in cervical degenerative population treated with ACCF is a critical component to assist surgeons with the decision of whether or not to place a drain postoperatively. Although previous reports have challenged the efficacy of drains for many surgical procedures, little has assessed the necessity of drain use after ACCF [ 15 18 ]. This study compared the patients who underwent ACCF with increased surgical drain output and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that age was associated with an increased prevalence of increased drain output following spine surgery. Basques et al found that patients with age 50 years or more were more likely to have increased drain output following ACDF and deduced that this effect may be due to delayed wound healing associated with increased age [ 18 ]. Similarly, Sokolowski et al found that advanced age is an independent risk factor associated with postoperative hematoma volume.…”
Section: Discussionmentioning
confidence: 99%